2021
DOI: 10.1177/10778012211038969
|View full text |Cite
|
Sign up to set email alerts
|

“If not Mine, She Won't Belong to Another”: Mechanisms of Moral Disengagement in a Femicide Perpetrator from Brazil

Abstract: Case files can show how aggressors use different explanations to reduce the seriousness of their crime. We aimed to identify and categorize a 2016 Brazilian case file from a perpetrator of femicide, based on moral disengagement theory. Content analysis yielded 47 verbalized excerpts, with 70 disengagement occurrences. The most frequently used mechanisms throughout the aggressor's speeches consisted of moral justification and blaming the victim herself. Results indicated that he reduced the seriousness of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…At the time of the intimate femicide, most men felt a strong loss of control over their bodies, or that was at least how they interpreted these emotions in retrospect. While there is certainly an element of rationalisation and justification in such retrospective accounts (Di Marco and Evans, 2020;Hearn, 1998;Regis-Moura et al, 2022), the narratives nonetheless describe the intensity of the emotions of anger that participants experienced.…”
Section: Anger: Sparking the Femicidementioning
confidence: 99%
See 1 more Smart Citation
“…At the time of the intimate femicide, most men felt a strong loss of control over their bodies, or that was at least how they interpreted these emotions in retrospect. While there is certainly an element of rationalisation and justification in such retrospective accounts (Di Marco and Evans, 2020;Hearn, 1998;Regis-Moura et al, 2022), the narratives nonetheless describe the intensity of the emotions of anger that participants experienced.…”
Section: Anger: Sparking the Femicidementioning
confidence: 99%
“…More recently, there has been an emerging interest in the life histories, narratives, and sense-making of individuals who commit intimate femicide (Di Marco and Evans, 2020;Dobash and Dobash, 2015;Fahs et al, 2023;Mathews et al, 2011Mathews et al, , 2015Regis-Moura et al, 2022). Research has revealed that comprehending the worldviews of the perpetrators is key to preventing it, as such views may reveal the norms involved in aggression (Jewkes et al, 2015;Presser, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Importância desses estudos para a implementação e criação de programas de prevenção das violências nas escolas e na saúde (Condori, 2022;Regis-Moura et al, 2022) Outro ponto que merece atenção é o achado de que vítimas de violência e perpetradores apresentam altos níveis de DM. (Maftei e Dănilă, 2023;Seminario, 2023).…”
Section: Recomendaçõesunclassified
“…Essas estratégias educacionais têm o potencial de reduzir a acessibilidade aos mecanismos de DM, a tolerância e a propensão do IBAS(Pina et al, 2021) e deveriam focar, também, em explorar formas construtivas de interação online e os danos que essas interações têm para além da vida virtual(Paciello et al, 2021).Para estratégias de prevenção mais eficazes -nos crimes de feminicídio -é fundamental a compreensão do fenômeno na perspectiva dos perpetradores, das características da interação verbal e não-verbal com as suas vítimas, bem como de outros elementos situacionais do crime. (Regis-Moura et al, 2022). Para a construção de programas de intervenção com os agressores é necessário que se considere o DM, infidelidade, uso da pornografia, gênero, gestão da raiva e resolução eficaz de conflitos (D'Urso et al, 2019; Ferreiros e Clemente, 2022;Maglinte et al, 2016; Rollero e De Piccoli, 2020).…”
unclassified
“…En estos casos, los temas más recurrentes en sus relatos son: (1) la víctima ocasionó el incidente denunciado, (2) el varón actuó en defensa propia, (3) el incidente no debería ser considerado como violencia en tanto que no existió una agresión física o esta fue mínima y (4) la negación del asalto ( A su vez, estudios socio-narrativos han mostrado cómo el análisis de los relatos de los agresores abre camino a la comprensión de la violencia. Por ejemplo, se ha mostrado cómo las narrativas explicativas con las que se da sentido a la violencia letal (Di Marco & Evans, 2020) y no letal (Hearn, 1988;Presser, 2008), las estrategias de desvinculación moral de perpetradores de femicidio (Regis-Moura et al, 2021) y modos en los que se describe a las mujeres a partir de la amenaza, el control y el contexto sirven para comprender las condiciones en las que se basa la violencia de género.…”
Section: Técnicas De Neutralización Y Violencia De Génerounclassified